Developing poor communities through creative tourism - Dias, Á.; Maria Rosario González-Rodríguez; Patuleia, M. (Journal of Tourism and Cultural Change, 2021)
The research on creative tourism is mainly focused on developed western economies. Studies about developing countries with a significant percentage of the population living in poverty are still scarce. As such, this study is based on extensive field research and in-depth interviews of four poor communities in two countries (Brazil and Peru). The main goal is to identify a group of factors and their inter-relation as they contribute to the development of poor communities using creative tourism approaches. The results point to a positive response, i.e., it is possible for poor communities to offer interactive experiences. But not directly. Instead, there are a number of requirements that contribute to this accomplishment. First, local development depends on the involvement of external entities. Their role includes not only the achievement of consensus but also the allocation of capital, skills and resources. Second, initial results develop entrepreneurial initiatives with a direct impact on further investments, especially in tourism. Third, tourism-related processes result from other non-tourism activities. However, tourism activities benefit from (1) the gains in popularity of the region and/or its products, traditions and culture; (2) increase in entrepreneurial activity.